Performance dependence of thermosyphon on the functionalization approaches: An experimental study on thermo-physical properties of graphene nanoplatelet-based water nanofluids. (1st March 2015) - Amiri, Ahmad; Sadri, Rad; Shanbedi, Mehdi; Ahmadi, Goodarz; Chew, B.T.; Kazi, S.N.; Dahari, Mahidzal
Highlights: Highly dispersed GNP-based water nanofluids are prepared with the microwave-assisted method. Rheological and thermo-physical properties of all treated samples are shown good enhancements. Different heat transfer parameters are investigated in a thermosyphon. An industrially scalable and cost-effective route is introduced. Abstract: Graphene Nanoplatelets (GNP) were stably dispersed in aqueous media by covalent and non-covalent functionalization. Covalent functionalization was performed by a rapid microwave-assisted approach. Surface functionality groups and morphology of acid-treated GNP were analyzed by Fourier transform infrared spectroscopy and transmission electron microscopy. The GNP-based water nanofluids were then prepared with different concentrations of GNP to evaluate the thermo-physical and rheological properties. It was found that the rheological and thermo-physical properties of all treated samples were significantly enhanced compared to the pure water. The amount of enhancement also increased as the weight concentration increased. Thermo-physical results also confirmed that the thermal conductivity varied significantly depending on the functionalization approaches. At a constant concentration, the measurement showed that the thermal conductivity of covalent nanofluid (GNP-COOH/water) is larger than the non-covalent nanofluid (GNP-SDBS/water), which is larger than distilled water. The GNP-COOH/water nanofluids were found to be especially more effective in the thermosyphon in terms of overall thermal properties such as net heat transfer, entropy, and thermal efficiency, and rheological property such as effective viscosity, as well as, total pressure drop in comparison to GNP-SDBS/water nanofluids and certainly distilled water. The relative degradation of thermal conductivity and heat transfer efficiency of non-covalent nanofluids (GNP-SDBS/water) is due to the reduction of effective heat transfer surface of GNP nanoparticles in suspension, implying lower formation of surface nanolayers. Since the covalent functionalization with microwave radiation is a fast and cost-effective, it would provide an economical approach for industrial applications, an environmentally friendly alternative to the surfactant methods.